Is Managerial Authority Still Human? Algorithmic Management and the Reconfiguration of Authority - Nouamani, Said; Asri, Hayat El (Journal of Knowledge Management Practice, 2026)
The integration of algorithmic systems into organizational processes is reshaping not only how work is  coordinated but also the foundations of managerial authority. Research on algorithmic management has  largely concentrated on labor control, surveillance, and worker outcomes. Yet, it has paid less attention to  the ways in which these systems transform authority as an institutional feature of organizations. This article  develops a conceptual framework that explains how authority shifts across sociotechnical systems that  include managerial actors, data infrastructures, and computational models. It draws on organization  theory and sociotechnical perspectives to argue that managerial authority does not reside solely in formal  roles but takes shape through ongoing interactions with algorithmic systems. Authority, in this view,  emerges through practice rather than remaining fixed within hierarchical structures. The paper proposes  a typology of hybrid managerial authority regimes, each defined by a different balance between managerial  discretion and algorithmic decision-making. It also distinguishes algorithmic authority from algorithmic  control, showing that algorithmic outputs can function as legitimate bases for decision-making rather than  serving only as tools of monitoring or enforcement. These arguments contribute to research on digital  organizing and AI governance, especially in relation to the evolution of authority, legitimacy, and  accountability in organizations that rely on algorithmic systems. The analysis also calls into question  established assumptions about hierarchical authority in contexts where governance increasingly operates  through computational infrastructures.
Keywords: knowledge management; algorithmic management; managerial authority; algorithmic governance; sociotechnical systems; digital organizations